Efektivitas Media Sosial Instagram Terhadap Personal Branding Bintang Emon Pada Pengguna Instagram - Amarilia Shinta; K. Y. S. Putri (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT Currently, the popularity of Instagram is used by many people to get information or to share information about themselves. In today's era, Instagram has been used as a media for forming a person's self-image, this can be seen by the posts they upload on their Instagram account. The same thing was done by comedian Bintang Emon to make Instagram a place for the formation of self-image (personal branding). The aim of this research is to find out how much the effectiveness of Instagram social media on Bintang Emon personal branding on Instagram users. The research method that researchers chose was survey research. The paradigm used in this research is the positivism paradigm, according to the paradigm used, the approach to this research is descriptive quantitative. In this study, researchers conducted survey research by distributing questionnaires via google form to Instagram users and also watching video content owned by Bintang Emon. This study uses personal branding theory popularized by Peter Montoya and effective communication (Stewart L. Tubbs). The results of this study reveal that there is an effect of the effectiveness of Instagram social media on the personal branding of Bintang Emon by 64.3%. The conclusion results of this study are that there is a significant effect, namely the value of 0.000, and the results of the t-test and t table that the researchers obtained are T count> T table 14,324> 1,98099 so that there is an influence between the effectiveness of Instagram social media Instagram and Bintang Emon personal branding on Instagram users. Keywords: Bintang Emon; Effective Communication; Personal Branding